2023
DOI: 10.3390/ma17010015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Poly-γ-Glutamic Acid and Its Application in Biomedical Materials

Minjian Cai,
Yumin Han,
Xianhong Zheng
et al.

Abstract: Poly-γ-glutamic acid (γ-PGA) is a natural polymer composed of glutamic acid monomer and it has garnered substantial attention in both the fields of material science and biomedicine. Its remarkable cell compatibility, degradability, and other advantageous characteristics have made it a vital component in the medical field. In this comprehensive review, we delve into the production methods, primary application forms, and medical applications of γ-PGA, drawing from numerous prior studies. Among the four productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…The fundamental research target for industrial application is to optimize the fermentation medium in order to decrease the costs of biopolymer manufacturing. Nevertheless, the production costs of γ-PGA are considerably decreased as they do not need the inclusion of external glutamate ( Cai et al, 2023 ). However, the major economic problem in γ-PGA production is the high cost associated with the media components and the kind of microorganisms used have a significant impact on production costs.…”
Section: Limitations and Commercialization Strategies Of γ-Pga Produc...mentioning
confidence: 99%
See 3 more Smart Citations
“…The fundamental research target for industrial application is to optimize the fermentation medium in order to decrease the costs of biopolymer manufacturing. Nevertheless, the production costs of γ-PGA are considerably decreased as they do not need the inclusion of external glutamate ( Cai et al, 2023 ). However, the major economic problem in γ-PGA production is the high cost associated with the media components and the kind of microorganisms used have a significant impact on production costs.…”
Section: Limitations and Commercialization Strategies Of γ-Pga Produc...mentioning
confidence: 99%
“…γ-PGA has a wide range of applications in pharmaceutical manufacturing including delivery systems, tissue engineering, gene carriers, and therapeutic and immunological effects. It can significantly reduce drug toxicity and improve drug efficiency in combination with other matters ( Luo et al, 2016 ; Zhan et al, 2018 ; Cai et al, 2023 ). However, molecular weight is a decisive factor for drug-delivery properties such as the controlled and delayed release of drugs ( Luo et al, 2016 ).…”
Section: Applications Of γ-Pgamentioning
confidence: 99%
See 2 more Smart Citations
“…Further studies, such as those conducted by Shin-An Yang et al [61,62], explored the formulations of cosmetic products containing poly-γ-glutamic acid within specific concentrations and molecular weights. Their results demonstrated that PGA formulations promoted cell growth in fibroblast and keratinocyte cells, indicating biocompatibility and potential wound-healing properties.…”
Section: The Potential Of Poly-γ-glutamic Acid As a Moisturizing And ...mentioning
confidence: 99%